Existential phenomenological view of health care experiences from the perspective of cancer survivors - Kelly Cristine Piolli Alvarez; Catarina Aparecida Sales (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to understand the experience of post-discharge health care of primary cancer treatment from the perspective of survivors. Methods: a descriptive study with a qualitative approach, using Martin Heidegger's Existential Phenomenology framework. Analysis of semi-structured interviews of 11 cancer survivors, after primary treatment, was carried out through vague and median and hermeneutic understanding. Results: three units of meaning emerged in the search for the unveiling of the phenomenon: Respecting physical limitations after cancer; Transcending themselves after illness; and Overcoming the ghost of fear. Final Considerations: cancer survivors experience care in intentional choices favorable to health, when they overcome their own limitations, fear of relapse or new cancer. The need to improve continuous professional monitoring in order to answer questions reinforce favorable attitudes and enhance the chances of better quality of life for cancer survivors.